PKM PENGOLAHAN LIMBAH CANGKANG KERANG MENJADI CINDERAMATA DITENGAH PANDEMI COVID-19 DI KARANGANTU KELURAHAN BANTEN - Andi Hasryningsih Asfar; Nita Wahyuni; Anisa Paradila; Elsa Putri Indira; Putri Alfitriani (Yayasan Education and Social Center, 2021)
Banten Village, which is located in the Kasemen District, Serang City, Banten Province, is a coastal area that has considerable potential, especially in the field of fisheries. Marine products are the main source of livelihood for the majority of the population. Shellfish is one of the fishery products that is quite large, but only the meat is used so that the skin or shell becomes unused waste. With this potential waste, the Uniba Group 04 Student PKM program utilizes the development of shellfish waste into souvenirs which are expected to contribute to economic improvement for the Karangantu community, Banten Village by conducting counseling, discussions and training for community members who are interested in this activity. It is hoped that this activity will continue and be continued by the participants in order to become a business area that can improve the family's economy, supported by online-based marketing amidst the COVID-19 pandemic, which is still not moving from Indonesia